Presence of two plume-related volcanic events along the Indian northern passive margin evidenced by the geochemistry of the Carboniferous Baralacha La dykes, the Permian Panjal traps and the Drakkar Po phonolites - Chauvet, F; Lapierre, H; Bosch, D; Bussy, F; Vannay, JC; Mascle, GH; Brunet, P; Cotten, J; Keller, F (Himalayan Journal of Sciences, 2008)
Himalayan Journal of Sciences Vol.2(4) Special Issue 2004 pp. 113